Gestión Financiera en la piladora ALROSA de la ciudad de Babahoyo durante los periodos 2022-2023. - Gavilánez Piza, María Gabriela (2024)
Financial management at the business level facilitates a diversity of benefits through techniques and methods that can be applied critically, it provides the correct management of countless resources that are at hand in a company, many privileges will be executed with the purpose to increase its value, positive aspects for collaborators, possible investors and the first in the hierarchy of the organization, on the other hand, accounting administration, enables good management and correct interpretation of the information in the accounting documents that are presents to the board of directors. Due to the aforementioned, an exhaustive analysis was carried out on the financial management of the ALROSA pillar, in order to evaluate the different accounting policies it maintains and it was possible to see the ability to make informed strategic decisions will be significantly benefited by a robust accounting infrastructure, the availability Timely and accurate financial information will allow the company to respond quickly to market changes and capitalize on growth opportunities more effectively. This is crucial to maintaining competitiveness in the dynamic agricultural sector in and around Babahoyo. Finally, a mixed approach was applied to collect quantitative and qualitative data that help carry out a detailed evaluation of the economic situation of the organization and in turn find gaps that affect the company negatively in the long term.